Ion Microbeam Studies of Charge Transport in Semiconductor Radiation Detectors With Three-Dimensional Structures: An Example of LGAD - Jakšić, Milko; Crnjac, Andreo; Kramberger, Gregor; Manojlović, Miloš; Laštovička-Medin, Gordana; Ramos, Mauricio Rodriguez (Frontiers in Physics, 2022)
The development of semiconductor detectors with an increased tolerance to high radiation levels often results in devices that deviate significantly from those of the classical design with planar electrodes. Decreasing the charge drift distance and/or introducing localised charge multiplication volumes are two detector development strategies that are often used in an attempt to increase the device radiation hardness. However, such approaches result in a more complex three-dimensional distribution of electrodes and sensitive detector volumes, which presents a challenge for the microscopic characterisation of charge transport properties. IBIC (ion beam-induced charge) is one of the available microscopic characterisation techniques that utilises focused, MeV energy range ions to probe charge transport. Here we used IBIC to probe different detector depths by varying the ion energy and/or angle of incidence and to probe certain detector regions by ions of the same range but with different stopping powers. These investigations are particularly important for studying low gain avalanche diode (LGAD) detectors, where measured interpad distances change with proton energy and where an increased carrier density results in changes in the charge multiplication, which are studied in this work.